Boron removal from produced water using electrocoagulation - Ezechi, E.H. (Institution of Chemical Engineers, 2014)
Produced water is the largest wastestream of oil and gas exploration but its chemical composition hinders its beneficial use. Effective treatment and reuse of produced water can mitigate scarcity of fresh water, especially in arid areas. Presence of inorganic compounds such as boron in produced water renders its beneficial use difficult. In this study, boron removal from produced water was investigated. Synthetic wastewater was prepared simulating the range of boron concentrations in produced water. Four operating parameters pH (3-11), charge loading (1200-3600 Ah/m3), contact time (15-90 min) and concentration (10-30 mg/L) were selected and their optimum conditions investigated. The obtained optimum conditions were applied to treat real produced water. Residual boron concentration of 0.3 mg/L was obtained from initial boron concentration of 15 mg/L in real produced water at optimum conditions of pH 7, charge loading 2400 Ah/m3 and contact time 90 min. Boron adsorption could be represented by Langmuir and Freundlich isotherm models. Electrocoagulation can be used for the effective removal of boron from produced water. Â© 2014 The Institution of Chemical Engineers.